MultiFEBE: A multi-domain finite element–boundary element solver for linear mixed-dimensional mechanical problems - Jacob D.R. Bordón; Guillermo M. Álamo; Luis A. Padrón; Juan J. Aznárez; Orlando Maeso (SoftwareX, 2022)
MultiFEBE integrates multiple finite element and boundary element models for solving linear static and time harmonic multi-domain interaction problems within the field of computational mechanics. It allows to couple bounded or unbounded two- and three-dimensional continuum inviscid fluids, elastic solids or poroelastic media with beam and shell structural elements. This paper summarizes the models and numerical methods implemented in the code, and illustrates its use and capabilities through the computation of the dynamic response of the support structure of an offshore wind turbine fixed to the seabed through a jacket structure and three suction caissons.